Factors Effective in Creating Induced Demand for Medicine in Iran from the Experts\' Point of View - MR Pasha-Zanosi; Gh Mahmoodi; MA Jahani (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Pharmaceutical costs account for a major part of health-related costs, and the induced demand for medicine imposes a large financial and economic burden on individuals and the whole society. Therefore, the aim of the present study is to identify the factors effective in creating induced demand for medicine in Iran. Methods: This study is based on grounded theory approach and it was conducted in 2022. The interview questions were semi-structured and asked by experts. The initial selection of the samples was based on targeted sampling from among experts and scholars in the field of medicine and treatment from all over the country. The snowball method was used to increase the sample volume until it reached sufficiency. This research was completed by interviewing 20 experts. Findings: The key factors effective in creating induced demand were identified in the form of 4 themes, 8 categories and 31 subcategories. The extracted themes included social, structural-organizational, economic and beneficiary-related factors. Social factors included the categories of society's culture and pharmaceutical literacy, structural-organizational factors included the categories of regulatory mechanisms and educational and political factors, economic factors included the categories of payment and insurance systems, and finally the beneficiary-related factors included the categories of suppliers and demanders. Conclusion: Based on the results of this study, several factors play a role in the creation of induced demand for medicine, and following these factors can help policymakers formulate appropriate strategies to reduce unnecessary medicine prescription.